CONTENT ANALYSIS OF SPICE UP THE WORLD CAMPAIGN CONTENT ON GOOGLE ARTS AND CULTURE PLATFORM: Analisis Isi Konten Kampanye Spice Up The World Pada Platform Google Arts and Culture - Nugraha, Farhan Rizqullah; Mardiana, Lisa; Kumalasari, Astini (Jurnal Komunikasi Korporasi dan Media (JASIMA), 2023)
The decline in the glory of Indonesian spices has made the government want to restore the glory of spices to the past. The government has created a campaign program called Spice Up The World in collaboration with Google, where the campaign is in the form of content uploaded to the Google Arts and Culture platform. The choice of cooperation and the use of these platforms is more effective because the content is connected to the internet, technology and is free of charge. So that it can be reached by the world community. The purpose of this study is to analyze the contents of the Spice Up The World campaign content on the Google Arts and Culture platform and to find out the contents of the message and the message form of the campaign contents. This study used a content analysis research method with a descriptive approach. This study uses the theory of digital communication, campaigns, and 7C content analysis. Primary data was obtained from collecting Spice Up The World content documents in the form of images, symbols, text and so on using a coding method that describes the meaning of the various functions, themes and visual forms of the content. The results of the study show that 1) the form of the message is presented in the form of photos, drawings, illustrations, sound infographics, and videos, 2) the content of the message is additional information (knowledge) for the reader.